PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Saputra, Arif Reza Ady; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The aim of this study to determine the influences of corporate social responsibility (CSR) and provitability toward companies value of basic industry sector and chemistery which is listed on Indonesia Stock Excange. Ratio corporate social responsibility (CSR) as independent variabel uses index corporate social responsibility disclosure companies. Provitability ratio which is used as independent variabel are return on equity (ROE) and return on investment (ROI). While the value companies as dependent variabel measured by ratio price book value (PBV) and ratio tobin’s Q.In this study, the data where financial report and annual report. The sampling taken by purposive sampling, the sample are 12 from 64 basic industry companies and chemistery which is listed on Indonesia Stock Excange. Analysis techniques in this study are simple linear, double linear, determinate coefficient, test t (partial), and test F (simultan). Data analysis was used analysis linear agression with the help of software SPSS 21.The result of this study show that corporate social responsibility (CSR) on partial (test t) have significant effect toward companies value. While provitability also have significant effect toward companies value. The result on simultan (test F) shows there is significant effect between corporate social responsibility (CSR) and provitability as together toward companies value basic industry sector and chemistery which is listed on Indonesia Stock Excange.Keyword: Corporate Social Responsibility, Provitability, The Companies Value